2011
DOI: 10.1249/mss.0b013e31820e5adc
|View full text |Cite
|
Sign up to set email alerts
|

Montmorency Cherry Juice Reduces Muscle Damage Caused by Intensive Strength Exercise

Abstract: Montmorency cherry juice consumption improved the recovery of isometric muscle strength after intensive exercise perhaps owing to the attenuation of the oxidative damage induced by the damaging exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
263
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(298 citation statements)
references
References 38 publications
26
263
7
2
Order By: Relevance
“…Knee extension maximum voluntary contraction recovery was 90.9% of baseline at 24 hours and 92.9% of baseline at 48 hours in in the cherry group, compared to 84.9% and 88.5% in the placebo group, respectively. There was no significant reduction in muscle soreness because the cherry group had no change in muscle pressure pain threshold (reduction a maximum of 27%) [22]. Protein carbonyls were statistically elevated at baseline, which could have been a confounder indicating increased oxidative damage in the cherry group.…”
Section: Tart Cherry Pain and Muscle Damagementioning
confidence: 89%
See 4 more Smart Citations
“…Knee extension maximum voluntary contraction recovery was 90.9% of baseline at 24 hours and 92.9% of baseline at 48 hours in in the cherry group, compared to 84.9% and 88.5% in the placebo group, respectively. There was no significant reduction in muscle soreness because the cherry group had no change in muscle pressure pain threshold (reduction a maximum of 27%) [22]. Protein carbonyls were statistically elevated at baseline, which could have been a confounder indicating increased oxidative damage in the cherry group.…”
Section: Tart Cherry Pain and Muscle Damagementioning
confidence: 89%
“…A small study of 10 male athletes demonstrated that consumption of a tart cherry juice concentrate resulted in greater muscle force recovery with decreased serum protein carbonyls associated with reduced oxidative damage [22]. Knee extension maximum voluntary contraction recovery was 90.9% of baseline at 24 hours and 92.9% of baseline at 48 hours in in the cherry group, compared to 84.9% and 88.5% in the placebo group, respectively.…”
Section: Tart Cherry Pain and Muscle Damagementioning
confidence: 99%
See 3 more Smart Citations